Understanding life satisfaction among the original inhabitants in the suburbanized areas at the outskirts of a major city: a qualitative study - Celestin Ndikumana (International Journal of Qualitative Studies on Health & Well-Being)
Purpose Suburbanization has become a major characteristic of urban development in sub-Saharan Africa, and shifting from agricultural-based areas modus vivendi to urban lifestyles affects subjective wellbeing of the original settlers. While there is lack of evidence in the literature of wellbeing in these areas, this study examines life satisfaction of these populations by means of individuals’ own appreciation and evaluation of quality of life. Methods The study uses interpretionist and reflexive approaches, and analyses 76 interviews conducted through snowball sampling in two major suburbanized areas. Thematic analysis was used to analyse the data. Results Generally, the findings show that respondents are satisfied with material living conditions due to improvement of availability of economic opportunities, roads and other transport services, social and community support. However, income inequality and urban poverty result in the inability to afford modern and high-quality urban living conditions, which creates feelings of vulnerability while limiting social relationships. Conclusions There is a need to strenghten existing frameworks to fully respond to urban life requirements that relate to transport, education, hygiene, and sanitation services. It is also important to develop support systems that mitigate issues of gender discrimination, human rights, household decision-making, fashion, and cultural norms.